The manager's bookshelf a mosaic of contemporary views - Pierce, Jon L.; Newstrom, John W. (Pearson education, Inc., 2014)
This is a collection of objective summaries from a broad sampling of bestselling business books. Presenting readers with a collage of information to improve their knowledge of management practices, this text introduces the philosophies, views, and experiences of several authors whose works have captivated the attention of today's management community.